Transitions of cloud‐topped marine boundary layers characterized by AIRS, MODIS, and a large eddy simulation model. Issue 15 (14th August 2013) - Yue, Qing; Kahn, Brian H.; Xiao, Heng; Schreier, Mathias M.; Fetzer, Eric J.; Teixeira, João; Sušelj, Kay
Abstract : [1] Cloud top entrainment instability (CTEI) is a hypothesized positive feedback between entrainment mixing and evaporative cooling near the cloud top. Previous theoretical and numerical modeling studies have shown that the persistence or breakup of marine boundary layer (MBL) clouds may be sensitive to the CTEI parameter. Collocated thermodynamic profile and cloud observations obtained from the Atmospheric Infrared Sounder (AIRS) and Moderate Resolution Imaging Spectroradiometer (MODIS) instruments are used to quantify the relationship between the CTEI parameter and the cloud‐topped MBL transition from stratocumulus to trade cumulus in the northeastern Pacific Ocean. Results derived from AIRS and MODIS are compared with numerical results from the UCLA large eddy simulation (LES) model for both well‐mixed and decoupled MBLs. The satellite and model results both demonstrate a clear correlation between the CTEI parameter and MBL cloud fraction. Despite fundamental differences between LES steady state results and the instantaneous snapshot type of observations from satellites, significant correlations for both the instantaneous pixel‐scale observations and the long‐term averaged spatial patterns between the CTEI parameter and MBL cloud fraction are found from the satellite observations and are consistent with LES results. This suggests the potential of using AIRS and MODIS to quantify global and temporal characteristics of the cloud‐topped MBL transition. Key Points: The MBL transition is studied using AIRS/MODIS observations and UCLA LES. MBL cloud fraction is closely correlated with CTEI parameter. This work shows the potential of using AIRS/MODIS to study MBL transition.